Viabilidade do uso do biogás da bovinocultura e suinocultura para geração de energia elétrica e irrigação em propriedades rurais - Coldebella, Anderson (2006)
The present work had as an objective to evaluate the viability of the use of biogas proceeding from the activities of bovine culture of milk and swine culture in sets motor generator and motor bomb to the irrigation in agricultural properties. The experiment was done in the city of Toledo/PR, in two different properties, one with its activities directed to the bovine culture of milk with 130 animals in a regimen of confinement and the other property with its activities directed to the swine culture, working as a pig producer unit with a breeding of 1,000 breeders. Both of the properties use biodigestors to the treatment of the generated effluents and they have as byproducts the biogas and the biofertilizer. To establish the consumption of biogas per HP/hour it was used a compressor to supply a bag named gas-tank. With the amount of biogas known inside the gas-tank, it was connected to the engines, which remained working until the consumption of all the biogas. To the biogas from the bovine culture the consumption was of 0,981 m3/HP/hour to the set of motor bomb and of 2,77 m3/HP/hour to the set of motor generator, while that for the biogas from swine culture the consumption was of 1,113 m3 /HP/hour and 0,791 m3/HP/hour to motor generator and motor bomb respectively. The efficiency to the power production was of 4.14% to the biogas from bovines and of 10,3% to the biogas from swines. Considering the time of amortization of 10 years, the cost of the biogas was of R$ 0,229 / m3 for bovines and of 0,063 / m3 for swines. The cost of the electrical power generated is related to the applying of the capacity of the plan and to the cost of biogas, to the biogas from the bovine culture the cost of the generated power was of R$ 465,07/MWh and to the biogas from swine culture the cost was of R$ 90,86/MWh, considering that both of the plans be operating fir 10 hours a day. The time of return for the investment depends on the initial investment and on the price of the electric power charged by the power company, with a tariff of R$ 300,00/MWh operating the generation system for four hours a day and considering the economy generated with the irrigation system, the time of return found was of 4.3 and 6.7 years to bovines and swines respectively. Besides that, the biofertilizer generated from bovines can fertilize 37 hectares a year and the biofertilizer generated from swines can fertilize 480 hectares a year. Despite the low levels of efficiency to power generation, the time of investment return is reasonable and it can become shorter if the economy generated by the use of the biofertilizer is considered.